2019
DOI: 10.1371/journal.pone.0224880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of neonatal fulminant necrotizing enterocolitis in a tertiary Children's hospital in the last 10 years

Abstract: The aim of this retrospective study was to explore the risk factors and clinical characteristics related to neonatal fulminant necrotizing enterocolitis (NEC). From 1 November 2007 to 31 October 2017, 352 neonates who were diagnosed with NEC (Bell stage ≥ΠB) and admitted to the Children’s Hospital of Chongqing Medical University were enrolled. Among these patients, 112 (31.82%) cases fulfilled the definition of fulminant NEC, and 62.5% (70/112) of fulminant cases presented a poor prognosis. All the survivors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
3
7
0
2
Order By: Relevance
“…In the present study, we showed an acute decrease in peripheral neutrophils limited to late pre-term/term cases. Similarly, in a cohort composed primary of late pre-term infants with NEC, there was a similar association between neutropenia (ANC <1.5 × 10 9 /L) and worse outcomes (7). Deviations in neutrophil count and function are seen in SGA infants (34, 35), and there was a higher proportion of SGA infants within the older (≥33 weeks) subgroup of our cohort.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, we showed an acute decrease in peripheral neutrophils limited to late pre-term/term cases. Similarly, in a cohort composed primary of late pre-term infants with NEC, there was a similar association between neutropenia (ANC <1.5 × 10 9 /L) and worse outcomes (7). Deviations in neutrophil count and function are seen in SGA infants (34, 35), and there was a higher proportion of SGA infants within the older (≥33 weeks) subgroup of our cohort.…”
Section: Discussionsupporting
confidence: 75%
“…Prior studies have shown that an acute drop from baseline in monocyte count is suggestive of NEC diagnosis (4,5). Similarly, neutropenia at illness onset is seen in severe NEC and is associated with greater extent of disease and surgical intervention (6)(7)(8). A number of studies have suggested that alterations in lymphocytes are associated with NEC, although the data are mixed (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…응급실을 방문한 6-60개월 환자 중, 주증상이 "발작(seizure)", "경련(convulsion)", "열발작", "발작 후 상태"에 해당하거나, 퇴원진단이 "전신발작", "부분발작", "경련발작" 등 발작 관련 진단코드에 해당하는 환자를 추출했다. 추출한 환자 중에서 상기 포함 및 제외 기준을 고려하여 연구대상자를 선정했고, 연구 목적을 모르는 훈련된 연구자 1명이 표준화 서식을 이용하여 의무기록에서 다음과 같은 환자의 임상적 특성을 수집했다 5,[10][11][12][13][14] . 의무기록 내용이 불분명한 경우만 다른 연구자 2인과 상의하여 결정했다.…”
Section: 연구 방법unclassified
“…의무기록 내용이 불분명한 경우만 다른 연구자 2인과 상의하여 결정했다. 나이(월), 성별, 과거력, 가족력, 방문 당시 체온 40.0도 미만 5) , 열 발생 1시간 미만 5) , 1차 발작의 양상 및 동반 증상, 2차 발작 발생 전 최고 체온 40.0도 이상, 2차 발작 발생 시점, 응급실에서 시행한 첫 혈액검사에서 백혈구 수 < 6.0×10 9 /L 또는 > 15.5×10 9 /L 10) , 적혈구침강속도 > 10.0 mm/h 11) , C-반응단백질 > 10.0 mg/L 12) , 말초 정맥혈 pH < 7.31 13) , 탄산수소염 < 22.0 mmol/L 14) , 동일 Values are expressed as number only or number (%).…”
Section: 연구 방법unclassified
“…Apart from the highly fatal sub-population NEC described above, attention should be paid to those with a rapid course and lower mortality. Lin et al reported a sub-population of NEC, defined as patients who underwent intestinal surgical intervention within 48 h following NEC onset ( 6 ). Patients restricted to such a definition suffer from higher mortality than patients without a rapid course, but lower than that in a highly fatal sub-population, which is called fulminant NEC.…”
Section: Introductionmentioning
confidence: 99%